Can criminality be predicted based on facial appearance? - Ng, Wei Zhou (Nanyang Technological University, 2024)
Face-based trait inferences appeared in philosophy and the pseudoscience physiognomy. Recent research has shown that there are some evidences in the validity of inferring traits based on one’s facial appearance, with many studies showing high consensus of trait ratings among participants even without prior knowledge of the characteristics of the face that is perceived, as well as the fact that it is performed rapidly and effortlessly. As an extension of trait inferences of faces, a few studies performed inferences of criminality based on faces. As the literature regarding the topic was lacking, with majority based on the west, it provided a call to action to investigate whether these findings applied to the east as well. Investigation on whether the Asian population sample were able to identify criminals solely based on their facial appearance was tested, along with trait inferences of these faces. The study’s hypothesis holds true with criminality being able to be identified through faces at zero acquaintance, proving that faces do hold a kernel of truth to one’s inner workings. Perceptions of criminality was determined to be mediated by low trustworthiness and high dominance, with the research correlating highly with the findings of the west, lending possibility to the idea that face-based trait inferences are an innate, adaptive ability that humans have evolved together with. The findings act a further step to understanding face-trait links and the evolution of faces.